2013
DOI: 10.1002/jcb.24507
|View full text |Cite
|
Sign up to set email alerts
|

Muscle glycogen synthase isoform is responsible for testicular glycogen synthesis: Glycogen overproduction induces apoptosis in male germ cells

Abstract: Glycogen is the main source of glucose for many biological events. However, this molecule may have other functions, including those that have deleterious effects on cells. The rate-limiting enzyme in glycogen synthesis is glycogen synthase (GS). It is encoded by two genes, GYS1, expressed in muscle (muscle glycogen synthase, MGS) and other tissues, and GYS2, primarily expressed in liver (liver glycogen synthase, LGS). Expression of GS and its activity have been widely studied in many tissues. To date, it is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 48 publications
0
33
1
Order By: Relevance
“…This protein acts as a hub between glycogen synthase (GS), protein phosphatase 1 and glycogen to promote glycogen synthesis [15]. This strategy has been used to successfully enhance glycogen accumulation in several tissues [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…This protein acts as a hub between glycogen synthase (GS), protein phosphatase 1 and glycogen to promote glycogen synthesis [15]. This strategy has been used to successfully enhance glycogen accumulation in several tissues [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…We have suggested that our previous results observed in whole testis from the transgenic models could be explained by the pathway for glycogen synthesis (Villarroel‐Espíndola et al, ), which grows attached to the desmin and actin filaments and microtubules (Graham et al, ; Stapleton et al, ). Tight junctions and desmosome present in the blood‐testis barrier are stabilized by cytoskeleton proteins.…”
Section: Discussionmentioning
confidence: 78%
“…Previously, we have published that glycogen accumulation promotes apoptosis on male germ cells and testis degeneration (Villarroel‐Espíndola et al, ); however, the mechanism involved is not clear. We have evaluated if glucose polymer accumulation can induce a differential response in cells from the seminiferous tubules.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glycogen content in testis decreases from the first post‐natal day onwards, reaching values below 10 µg of glycogen/mg of protein after post‐natal day 10 [Villarroel‐Espíndola et al, ]. Sertoli cells are the main source of tubular glycogen when compared with germ cells [Villarroel‐Espíndola et al, ]. Nevertheless, Sertoli cell glycogen content is lower than muscle, adipose and hepatic cells.…”
mentioning
confidence: 99%